Transposable Elements: No More 'Junk DNA' - Yun-Ji Kim; Jungnam Lee; Kyudong Han (Genomics & Informatics)
Since the advent of whole-genome sequencing, transposable elements (TEs), just thought to be 'junk' DNA, have been noticed because of their numerous copies in various eukaryotic genomes. Many studies about TEs have been conducted to discover their functions in their host genomes. Based on the results of those studies, it has been generally accepted that they have a function to cause genomic and genetic variations. However, their infinite functions are not fully elucidated. Through various mechanisms, including de novo TE insertions, TE insertion-mediated deletions, and recombination events, they manipulate their host genomes. In this review, we focus on Alu, L1, human endogenous retrovirus, and short interspersed element/variable number of tandem repeats/Alu (SVA) elements and discuss how they have affected primate genomes, especially the human and chimpanzee genomes, since their divergence.